2018
DOI: 10.1051/0004-6361/201833378
|View full text |Cite
|
Sign up to set email alerts
|

Radio jets and gamma-ray emission in radio-silent narrow-line Seyfert 1 galaxies

Abstract: We have detected six narrow-line Seyfert 1 (NLS1) galaxies at 37 GHz that were previously classified as radio silent and two that were classified as radio quiet. These detections reveal the presumption that NLS1 galaxies labelled radio quiet or radio silent and hosted by spiral galaxies are unable to launch jets to be incorrect. The detections are a plausible indicator of the presence of a powerful, most likely relativistic jet because this intensity of emission at 37 GHz cannot be explained by, for example, r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 37 publications
3
90
0
Order By: Relevance
“…Nevertheless, we expect more sources to appear, as Fermi continues its measurements. Evidence for faint and/or sporadic γ-ray emission was reported for several more radioloud NLS1 galaxies ( [44], [94], [33], [105], [88]). [12] recently re-classified the optical spectrum Table 1: γ-ray emitting NLS1 galaxies, detected at high significance and published in main journals (see [44], [94], [33], [105], [12] and [88] for further candidates).…”
Section: γ-Ray Detection Of Radio-loud Nls1 Galaxiesmentioning
confidence: 83%
“…Nevertheless, we expect more sources to appear, as Fermi continues its measurements. Evidence for faint and/or sporadic γ-ray emission was reported for several more radioloud NLS1 galaxies ( [44], [94], [33], [105], [88]). [12] recently re-classified the optical spectrum Table 1: γ-ray emitting NLS1 galaxies, detected at high significance and published in main journals (see [44], [94], [33], [105], [12] and [88] for further candidates).…”
Section: γ-Ray Detection Of Radio-loud Nls1 Galaxiesmentioning
confidence: 83%
“…Since, in this work, we focus on objects with closely aligned jets, γ-ray detected CSS NLSy1s are not considered. Moreover, the γ-ray detection of SDSS J164100.10+345452.7, claimed by Lähteenmäki et al (2018), has not been confirmed (see, Ciprini & Fermi-LAT Collaboration 2018) and hence this object was also not included in our sample. circular regions on the same chip, avoiding contaminating sources.…”
Section: Hard X-raysmentioning
confidence: 99%
“…With Fermi/LAT, it was discovered that a few of the jetted NLS1 galaxies emit luminous γ-ray radiation, highly variable in some cases, and E-mail: yaosu@pku.edu.cn independently confirming the presence of powerful jets in some NLS1 galaxies (Abdo et al 2009b). Meanwhile, about 15 γ-ray emitting NLS1s have been identified (Abdo et al 2009a;Abdo et al 2009a;Foschini 2011;D'Ammando et al 2012;D'Ammando et al 2015;Yao et al 2015;Yang et al 2018;Paliya et al 2018;Lähteenmäki et al 2018; see Komossa 2018 andRomano et al 2018 for reviews).…”
Section: Introductionmentioning
confidence: 99%